WEBVTT
00:00:02.390 --> 00:00:12.630
Find the equation of the circle that passes through the points π΄: negative four, negative three; π΅: negative three, negative four; and πΆ: negative two, negative three.
00:00:14.590 --> 00:00:19.950
So we have the coordinates of three points on the circumference of a circle and weβre looking to find its equation.
00:00:21.300 --> 00:00:24.730
In order to do so, we need to recall a key circle theorem.
00:00:26.330 --> 00:00:29.060
Suppose you have two points on the circumference of a circle.
00:00:30.750 --> 00:00:47.860
If you join them together, you create a chord. if you then construct the perpendicular bisector of a chord, so that is the line that is both perpendicular to it at right angles and cutting it directly in half, then this line will always pass through the centre of the circle.
00:00:49.570 --> 00:00:52.470
However, we know three points on the circumference of the circle.
00:00:53.990 --> 00:01:11.440
So our approach is going to be this: weβll look at two of the chords π΄π΅, π΅πΆ and π΄πΆ, weβll find the equations of two of the perpendicular bisectors, weβll then solve them simultaneously to find the coordinates of the point where they meet, which will give us the coordinates of the centre of the circle.
00:01:13.510 --> 00:01:17.260
So I only need to use two of the chords, so Iβm gonna start with π΄π΅.
00:01:19.020 --> 00:01:24.410
So the perpendicular bisector, well because it bisects the chord, it passes through the midpoint.
00:01:24.410 --> 00:01:25.980
So we need that first of all.
00:01:27.630 --> 00:01:34.030
So the midpoint of π΄π΅ is negative four plus negative three over two, negative three plus negative four over two.
00:01:34.240 --> 00:01:39.160
And so this gives a midpoint with coordinates negative seven over two, negative seven over two.
00:01:41.150 --> 00:01:57.270
The slope is change in π¦ over change in π₯, so subtracting the coordinates of π΄ from those of π΅, I have negative four minus negative three over negative three minus negative four which is negative one over one and therefore simplifies to just negative one.
00:01:57.270 --> 00:02:04.110
Now thatβs the slope of the chord π΄π΅, and I want the slope of the perpendicular bisector.
00:02:04.390 --> 00:02:11.300
So the slope of a perpendicular line will be the negative reciprocal of this value, so itβs just one.
00:02:13.160 --> 00:02:16.180
So hereβs what we know about the perpendicular bisector of π΄π΅.
00:02:16.380 --> 00:02:23.060
It has a slope of one and it passes through the point with coordinates negative seven over two, negative seven over two.
00:02:24.640 --> 00:02:30.490
So if we recall the slope-intercept form of the equation of a line, it would be π¦ equals ππ₯ plus π.
00:02:30.720 --> 00:02:33.010
And here, π, our slope, is one.
00:02:34.740 --> 00:02:38.000
So the equation of our line is π¦ equals π₯ plus π.
00:02:39.740 --> 00:02:53.070
Now looking at the coordinates of the midpoint, which is a point on this line, we see the π₯ and π¦ are both the same; theyβre both negative seven over two, which means that the value of this constant, π, is equal to zero as π¦ and π₯ equal to each other.
00:02:54.600 --> 00:02:59.920
So we have the equation of the perpendicular bisector of π΄π΅, is just π¦ equals π₯.
00:03:01.610 --> 00:03:05.330
Next, letβs look at finding the perpendicular bisector of the chord π΄πΆ.
00:03:07.130 --> 00:03:15.410
Now these two points actually have the same π¦-coordinate of negative three, which means that the line joining these two points is a horizontal line.
00:03:16.880 --> 00:03:22.160
Therefore, the perpendicular bisector of this line will be a vertical line passing through the midpoint.
00:03:24.000 --> 00:03:34.830
The midpoint of π΄πΆ has coordinates negative four plus negative two over two, negative three plus negative three over two which is the point with coordinates negative three, negative three.
00:03:36.680 --> 00:03:47.250
Now weβve already discussed that the perpendicular bisector will be a vertical line as the chord itself is a horizontal line, and vertical lines have their equation of the form π₯ equals constant.
00:03:48.750 --> 00:03:56.420
As the π₯-coordinate of the point that this line passes through is negative three, the equation of this line must be: π₯ equals negative three.
00:03:58.260 --> 00:04:04.540
So now we have the equations of our two perpendicular bisectors, π₯ equals negative three and π¦ equals π₯.
00:04:04.910 --> 00:04:09.970
Remember, weβre looking to solve these simultaneously in order to find the coordinates of the centre of the circle.
00:04:11.470 --> 00:04:13.460
Well, theyβre quite straightforward equations to solve.
00:04:13.460 --> 00:04:23.340
We already know the value of π₯, and we know that π¦ is equal to π₯ which means that the point where these two lines meet must be the point with coordinates negative three, negative three.
00:04:24.740 --> 00:04:30.970
So this means that the centre of the circle whose equation weβre looking to find, is this point negative three, negative three.
00:04:32.710 --> 00:04:39.690
Next, we need to find the radius of the circle which, remember, is the distance between the centre and any of the points on the circumference.
00:04:41.130 --> 00:04:43.810
Letβs look at the distance between the centre and point π΄.
00:04:44.290 --> 00:04:48.980
They both have the same π¦-coordinate of negative three, which means theyβre on a horizontal line.
00:04:50.460 --> 00:04:58.840
Therefore, the distance between these two points is just the difference between the π₯-coordinates, and the difference between negative three and negative four is one.
00:05:00.410 --> 00:05:03.530
This means that the radius of our circle is one length unit.
00:05:04.920 --> 00:05:15.670
Now you can confirm this by looking at the distance between the centre and point πΆ which are also on a horizontal line, or you could use the distance formula to calculate the distance between the centre and point π΅.
00:05:15.870 --> 00:05:18.040
But in any case, weβll get this value of one.
00:05:19.640 --> 00:05:23.630
So now we know the centre and radius of the circle; we just need to find itβs equation.
00:05:25.340 --> 00:05:41.470
If we recall the standard form of the equation of a circle, the centre radius form, it tells us that if a circle has a centre with coordinates β, π and radius π, then its equation is: π₯ minus β all squared plus π¦ minus π all squared is equal to π squared.
00:05:43.220 --> 00:05:52.320
As we know both the centre and radius of our circle, we can just substitute the relevant values: β and π are both negative three, and π is one.
00:05:53.930 --> 00:06:00.830
So we have π₯ minus negative three all squared plus π¦ minus negative three all squared is equal to one squared.
00:06:02.410 --> 00:06:04.370
Finally, we can just neaten this up a little.
00:06:04.560 --> 00:06:08.690
When you are subtracting negative three, that is equivalent to adding three.
00:06:08.820 --> 00:06:13.030
So we can simplify both brackets, and also one squared is equal to one.
00:06:14.660 --> 00:06:16.350
And so we have our answer to the problem.
00:06:16.350 --> 00:06:24.370
The equation of the circle that passes through these two points is: π₯ plus three squared plus π¦ plus three squared is equal to one.